Organic Fertilizer and Oligochitosan to Increase The Growth of Elephant Foot Yam (Amorphophallus muelleri Blume) Plants - Rahmawati, Nini; Br Sinaga, Siti Zarah (Agrosains : Jurnal Penelitian Agronomi, 2025)
Increasing growth of elephant foot yam plants on ultisol  which is marginal soil can be attempted by application organic fertilizer in the form of tea waste compost and soaking bulbil as planting material using oligochitosan. This study aims to obtain the concentration of oligochitosan soaking and the dose of tea waste compost on the initial growth of elephant foot yam in Ultisol. This research was conducted on the land of Centre for Roots and Tuber Study Universitas Sumatera Utara, from October 2022 to January 2023. This study used a Randomized Block Design with 2 factors, namely the application of organic fertilizer doses (0; 39.25; 78.5; 117.75 tons/ha) and oligochitosan concentration (0; 1125; 2250; 3375 ppm). The results of the study showed application of organic fertilizer significantly accelerated the age of shoot emergence, increased plant height, stem diameter, age of bulbil emergence and number of bulbils. Soaking oligochitosan significantly increased plant height and number of bulbils. Based on this study, it is recommended to use organic fertilizer in the form of tea waste compost at a dose of 39.25 tons/ha and oligochitosan soaking with a concentration of 1125 ppm to increase the growth of elephant foot yam plants in Ultisol soil.